CYTOKINE STATUS IN HYPOCHROMIC ANEMIAS OF DIFFERENT GENESIS - Галина Северьевна Суржикова; Сатеник Аршавиловна Клочкова-Абельянц; Сергей Николаевич Филимонов (Медицина в Кузбассе, 2020)
Objective – to study the cytokine status of blood serum in hypochromic anemias of various origins.